Preparation method of MoS2 / Ni-MOLs heterojunction for promoting degradation of organic dye methylene blue
Through the preparation method of MoS2/Ni-MOLs heterojunction, the problem of low degradation efficiency of methylene blue in the prior art is solved, and an efficient and environmentally friendly dye degradation effect is achieved.
Patent Information
- Application Number
- CN202411955375.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to efficiently degrade the organic dye methylene blue, and the traditional methods have problems with high cost, low efficiency and environmental pollution.
By a preparation method for MoS2/Ni-MOLs heterojunction, MoS2 is modified on two-dimensional sheet Ni-MOLs to form stacked heterojunctions, which improves the light absorption capacity and the separation efficiency of photogenerated carriers, thereby promoting the degradation of methylene blue.
It has achieved efficient degradation of methylene blue in a short time, with better degradation efficiency than the prior art, simple process, low cost, and environmentally friendly.
Smart Images

Figure CN119746940A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of degradation of organic dye methylene blue, and in particular to a method for preparing a MoS2 / Ni-MOLs heterojunction for promoting degradation of the organic dye methylene blue. Background Art
[0002] my country's printing and dyeing technology has been developed for thousands of years. With the continuous innovation of technology, printing and dyeing technology has developed from natural dyes to chemical dyes. Although the cost and extraction difficulty are reduced, the problem that follows is the pollution of water resources by chemical products. According to relevant statistics, the total annual production of synthetic dyes and pigments in the world is 106 tons. Although the annual output of dyes in my country is decreasing year by year, it is still the largest producer and user in the world. There are more than 700 commonly used dyes. However, 5%-15% of the dyes will be lost in the process of synthesizing dyes, and some of the dyes will be lost in the process of dyeing. These dyes that are not fully utilized will be treated as wastewater. After being discharged into the water, they will form toxic or carcinogenic water quality that seriously endangers the health of people or organisms, and may also damage the local soil and disrupt the chemical balance of the soil.
[0003] Aromatic azo dyes (such as methylene blue) account for about half of the total market share in many industries such as papermaking, plastics, leather, food, cosmetics and pharmaceuticals, and are the most frequently used dyes. 2 Hybridization, this dye will cause DNA mutation and cause diseases when it enters the human body. This substance can easily cause three hazards during the degradation process. In order to deal with and degrade this type of dye, a higher chemical oxygen demand is required, which may lead to insufficient oxygen in the water, causing the organisms in this area to die of lack of oxygen. Therefore, the degradation of this type of dye is difficult.
[0004] The existing traditional methods for degrading organic synthetic dyes include adsorption, coagulation and microbial methods. Among them, adsorption has certain limitations, and aerosol substances or other impurities in the waste can easily make the adsorbent ineffective. The coagulation method is a process in which the colloidal pollutants and fine suspended matter in the water are destabilized and condensed into separable flocs under the action of the dissociation and hydrolysis products of the coagulant. It has high operating costs, a large amount of sludge, and difficulty in dehydration, and poor treatment effect on hydrophilic dyes. The microbial method uses microbial enzymes to oxidize or reduce dye molecules, destroy unsaturated bonds and chromophores, but microorganisms have certain requirements for nutrients, pH, temperature and other conditions, and it is difficult to adapt to the characteristics of printing and dyeing wastewater with large water quality fluctuations, a variety of dyes, and high toxicity. At the same time, it also has the disadvantages of large footprint, complex management, poor decolorization effect, and low COD removal rate.
[0005] Therefore, finding an efficient, green and simple method to treat methylene blue wastewater is of great significance both for environmental protection and human health. Environmentally friendly, economical and efficient photocatalytic technology to degrade dyes has attracted widespread attention. - and h + ), e on the conduction band CB - Will react with O2 on the semiconductor surface to produce O2 through a reduction process - These free radicals then combine with the captured electrons and produce hydrogen peroxide H2O2 and hydroxyl radicals ·OH. ·O2 - Both ·OH radicals are strong oxidants and are the main active species of oxygen (ROS) in the photocatalytic degradation of organic pollutants. They can mineralize dyes and antibiotics into small molecules (such as H2O, CO2, etc.).
[0006] However, existing photocatalysts face the following problems: (1) There is recombination between photogenerated electron-hole pairs. When the recombination is too fast, the photogenerated electrons will not be able to complete the degradation; (2) The efficiency of photocatalysts in utilizing sunlight is not high, resulting in only a portion of the energy being absorbed, which greatly reduces the degradation rate.
[0007] Among them, in the reference (Heliyon, 2024, 10, e29204), methylene blue was degraded, WO / MoS / FTO (fluorine-doped tin oxide) was used as a photocathode, and the degradation rate of methylene blue reached 84.56% in 12 hours, while the degradation time used by the present invention at the same degradation efficiency was much less than that of the reference. In the reference (Materials Today Chemistry, 2024, 40, 102248), 3D printing technology was used to manufacture MOF / MoS aerogels, and the synthesis process was too complicated, and the degradation rate of methylene blue reached 95.86% within 1800 minutes. In the present invention, MoS2 was modified on two-dimensional sheet-like Ni-MOLs through a simple one-pot hydrothermal reaction, and the materials used in the process were simple and pollution-free. Therefore, the FQDS / MIL photocatalyst prepared in this work has better catalytic activity and environmental friendliness.
[0008] The present invention uses a semiconductor coupling method to modify MoS2 on Ni-MOLs and form a heterojunction for degrading methylene blue, which can not only improve the light absorption capacity of Ni-MOLs and the separation efficiency of photogenerated carriers, but also enhance the adsorption of dyes, thereby improving the degradation efficiency of methylene blue. The photocatalyst is simple to prepare, low in cost, and easy to recycle. Summary of the invention
[0009] In view of this, the present invention provides a method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue.
[0010] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0011] A method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue, characterized in that it comprises the following steps:
[0012] Step 1: Preparation of Ni-MOLs
[0013] Nickel nitrate hexahydrate and terephthalic acid were added to N,N-dimethylformamide, deionized water containing NaOH was slowly added, magnetic stirring was performed until dissolved, the mixture was transferred to a reactor for reaction, and the light green precipitate was collected by centrifugation, washed with deionized water and anhydrous ethanol respectively, and dried to obtain Ni-MOLs;
[0014] Step 2: Preparation of MoS2 / Ni-MOLs
[0015] MOLs, Na2MoO4·2H2O and TAA were weighed, added into ultrapure water, transferred to a reactor for reaction, black precipitate was collected by filtration, washed repeatedly with ethanol and ultrapure water, and dried to obtain 0.5MoS2 / Ni-MOLs, MoS2 / Ni-MOLs and 1.5MoS2 / Ni-MOLs.
[0016] Preferably, in step 1, the concentration of nickel nitrate hexahydrate is 6 mmol, the concentration of terephthalic acid is 4 mmol, and the amount of N,N-dimethylformamide added is 150 mL.
[0017] Preferably, in step 1, the concentration of NaOH is 0.32 mmol, and the amount of deionized water added is 10 mL.
[0018] Preferably, in step 1, the reaction temperature of the reactor is 120° C. and the reaction time is 10 h.
[0019] Preferably, in step 1, the rotation speed is 8000 rpm; and the mixture is washed three times with deionized water and three times with anhydrous ethanol respectively.
[0020] Preferably, in step 1, the drying temperature is 60° C. and the drying time is 12 h.
[0021] Preferably, in step 2, the amount of MOLs added is 0.1 g; the amount of ultrapure water is 50 mL.
[0022] Preferably, in step 2, TAA is specifically a mass ratio of MOLs:MoS2=2:1, 2:2, 2:3.
[0023] Preferably, in step 2, the reaction temperature of the reactor is 200° C. and the reaction time is 8 h.
[0024] Preferably, in step 2, the drying temperature is 60° C. and the drying time is 12 h.
[0025] Compared with the prior art, the present invention has achieved the following technical effects:
[0026] (1) The present invention modifies MoS2 on two-dimensional flaky Ni-MOLs by a one-pot hydrothermal method, and finally synthesizes a stacked MoS2 / Ni-MOLs heterojunction; the two-dimensional flaky Ni-MOLs are used to increase the contact area with MoS2 and reduce the conduction path of photogenerated electrons, thereby promoting the photocatalytic degradation of methylene blue;
[0027] (2) The preparation process of the present invention is simple and has excellent degradation effect. After optimization of initial concentration and pH, 10 mg L -1 of methylene blue solution 99.47%;
[0028] (3) The present invention modifies MoS2 on two-dimensional flaky Ni-MOLs and couples them into heterojunctions, thereby improving the light absorption capacity of Ni-MOLs and the separation efficiency of photogenerated carriers, enhancing the stability of the composite material, and greatly improving the degradation efficiency of the catalyst; it is very helpful for the application design of photocatalytic coupling catalytic systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 (a) is the X-ray diffraction (XRD) pattern of the composite sample; (b) is the Fourier transform infrared (FT-IR) pattern;
[0030] Figure 2 (ac) are SEM images of MoS2, Ni-MOLs and MNM; (d) is the TEM image of the composite MNM; (e) is the HR-TEM image of the composite MNM; (fl) is the energy dispersive spectroscopy (EDS) image;
[0031] Figure 3 (a) is 10 mg L -1 Methylene blue degradation curve; (b) is first-order kinetics; (c) is the kinetic constant; (d) is the cyclic degradation experiment of methylene blue;
[0032] Figure 4 (a) is the degradation curve of different methylene blue concentrations; (b) is the first-order kinetics; (c) is the kinetic constant;
[0033] Figure 5 (a) is the degradation curve of MB at different solution pH; (b) is the first-order kinetics; (c) is the kinetic constant. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The present invention discloses a method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue, comprising the following steps:
[0036] Step 1: Preparation of Ni-MOLs
[0037] 6mmol nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and 4mmol terephthalic acid (H2BDC) were added to 150mL N,N-dimethylformamide (DMF), and 10mL deionized water containing 0.32mmol NaOH was slowly added, and magnetic stirring was applied until dissolved. The mixture was transferred to a reactor and reacted at 120℃ for 10h. The light green precipitate was collected by centrifugation at 8000rpm, washed three times with deionized water and anhydrous ethanol respectively, and dried at 60℃ for 12h.
[0038] Step 2: Preparation of MoS2 / Ni-MOLs
[0039] Weigh 0.1 g of MOLs and a certain mass of Na2MoO4·2H2O and TAA (mass ratio of MOLs:MoS2=2:1, 2:2, 2:3), add them into 50 mL of ultrapure water, transfer to a reactor and react at 200 °C for 8 h, collect the black precipitate by filtration, wash it repeatedly with ethanol and ultrapure water, and dry it at 60 °C for 12 h to obtain 0.5MoS2 / Ni-MOLs, MoS2 / Ni-MOLs and 1.5MoS2 / Ni-MOLs (0.5MNM, MNM, 1.5MNM).
[0040] Embodiment 1:
[0041] Structural and morphological characterization of MNM composites
[0042] First, the microstructure of the MNM composite material was analyzed by XRD. Figure 1 As shown in (a), the diffraction peaks of pure MoS2 at 2θ=14.4°, 32.8°, 36.0°, and 58.6° correspond to the crystal planes (002), (100), (102), and (110), respectively; in addition, the diffraction peaks of pure Ni-MOLs at 2θ=8.5° and 16.9° correspond to the (100) and (010) crystal planes of the structure, respectively, and the diffraction peaks of the composite sample MNM all contain the corresponding diffraction peaks of the two monomers.
[0043] Next, Fourier transform infrared (FT-IR) was used to analyze the frame vibration structure of MoS2, Ni-MOLs and MNM, as shown in Figure 2. Figure 1 (b) As shown; for pure MoS2, 3010-3710cm -1 The broad band in the range represents the -OH stretching vibration of water molecules adsorbed on the catalyst surface, 1630 cm -1 The broad absorption peak at 619 cm-1 corresponds to the stretching vibration of water molecules adsorbed on the surface and free hydroxyl groups (C=O). -1 A characteristic peak is shown at , which represents the characteristic vibration mode of Mo-S bond.
[0044] For Ni-MOLs and composite samples, the -1 The broad band in the range from 1383 to 1668 cm represents the adsorption of water molecules on the catalyst surface and the stretching vibration of -OH in MOF. -1 A series of peaks at 1269 cm-1 correspond to the characteristic vibration modes associated with the benzene ring and the carbonyl group; in addition, -1 The CO characteristic peak at indicates that the Ni-MOLs structure in MNM is completely preserved;
[0045] The results of XRD and FT-IR showed that the composites were successfully synthesized.
[0046] Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to observe the morphology of monomers and composites. Figure 2 As shown in (ac), it can be seen that MoS2 is a nanoflower assembled from nanosheets, with a size of about 500nm. Ni-MOLs are stacked in a two-dimensional sheet shape, and the sheet MoS2 is evenly loaded on the micron-sized Ni-MOLs sheet, which greatly reduces the transfer path of photogenerated carriers, thereby accelerating the separation of photogenerated carriers and having a larger contact area to more effectively degrade pollutants.
[0047] like Figure 2 As shown in (d), it can be seen that the complex MNM is stacked in sheets;
[0048] like Figure 2 As shown in (e), the lattice spacing of Ni-MOLs was measured to be 0.31nm, and the lattice spacing of MoS2 was measured to be 0.28nm, indicating that the composite was successfully prepared.
[0049] Energy dispersive spectroscopy (EDS) Figure 2 As shown in (fl), it shows that C, O, S, Ni, and Mo elements exist in the composite material MNM, and MoS2 is loaded on the surface of Ni-MOLs sheet, further confirming the successful synthesis of binary heterojunction MNM.
[0050] Embodiment 2:
[0051] Degradation performance of methylene blue in MNM composites
[0052] The performance of MoS2 / Ni-MOLs photocatalyst was evaluated by degrading methylene blue using a 300 W xenon lamp with a cutoff filter (λ ≥ 420 nm) as a visible light source.
[0053] Prepare 10 mg / L methylene blue simulated dye wastewater with a pH of 7.0, take 100 mL of simulated wastewater and add it into a 200 mL reactor. At room temperature, use 30 mg of photocatalyst to degrade methylene blue. Stir the solution in the dark for 60 minutes to balance the adsorption, and then carry out photocatalytic reaction under a 300 W xenon lamp and a 420 nm cutoff filter for 3 hours, and measure the absorbance every 30 minutes.
[0054] The remaining contaminants in the filtered methylene blue degradation solution were analyzed by UV-Vis spectrophotometer (λ=663 nm). (Before measuring the absorbance, the sample was filtered with a 0.45 μm syringe filter).
[0055] As a preferred embodiment of the present invention, the degradation rate calculation formula of methylene blue is as follows:
[0056] D(%)=[(C0-C t ) / C0]×100%
[0057] Where C0 is the initial concentration of methylene blue, C t is the concentration of methylene blue after degradation.
[0058] Next, to evaluate the photocatalytic activity of the composite MNM, 30 mg of the catalyst was added to 100 mL of 10 mg L -1 Methylene blue solution.
[0059] like Figure 3 As shown in (a), after 60 minutes of adsorption equilibrium, 1.5MNM has the best adsorption performance, reaching a removal rate of 50.43%. After 180 minutes of visible light irradiation, the degradation rates of methylene blue by MoS2, Ni-MOLs, 0.5MNM, MNM and 1.5MNM are 84.97%, 72.65%, 89.17%, 96.72% and 92.28%, respectively. MNM has the best photocatalytic degradation effect, which is because too much MoS2 will block the active sites on Ni-MOLs, and too little MoS2 will greatly weaken the separation of photogenerated carriers.
[0060] Next, the degradation kinetics was studied and the first-order kinetic line of degradation was obtained, such as Figure 3As shown in (b), the slope of the first-order kinetic line of MNM is the largest, indicating that the degradation efficiency of MNM is the highest. In order to observe the slope change more intuitively, a kinetic constant bar graph was made, as shown in Figure 3 As shown in (c), it can be seen that the kinetic constants of the composite catalyst are larger than those of the two monomers. The maximum kinetic constant of MNM is 0.0162min -1 , respectively MoS2(0.00729min -1 ) and Ni-MOLs(000687min -1 ) are 2.22 and 2.36 times of that of Ni-MOLs. In summary, the composite of MoS2 and Ni-MOLs can greatly improve the photocatalytic efficiency.
[0061] In addition, the stability of the composite MNM was tested, e.g. Figure 3 (d) It can be seen that after five cycles, the degradation rate of the MNM composite material only decreased by 3%, indicating that MNM has good stability.
[0062] The present invention selects a methylene blue solution for a photocatalytic degradation experiment, weighs 100 mg of methylene blue, measures 1 L of distilled water with a measuring cylinder, prepares a 100 mg / L methylene blue solution, and puts the prepared solution into a volumetric flask for storage; dilutes the 100 mg / L methylene blue solution to 10, 15, 20, 25, and 30 mg / L, and pours the solution into a photocatalytic reaction container; weighs 30 mg of a photocatalyst and puts it into the same photocatalytic reaction container, draws a portion of the reaction solution with a syringe with a filter tip and injects it into a cuvette, and measures the concentration of the solution by using an ultraviolet spectrophotometer and records it as C0; wraps the photocatalytic reaction container with tin foil to carry out a dark reaction for 60 minutes, turns on a xenon lamp after the dark reaction stage is completed, reacts for 180 minutes under visible light, and measures the concentration of the solution by using the same operation every 30 minutes and records it as C t。
[0063] Next, the effect of different initial concentrations of MB solution on the degradation performance of the composite catalyst MNM was studied. Figure 4 As shown in (a), it can be seen that when the MB concentration increases from 10 mg L -1 Increased to 30 mg L -1 , the MB degradation rate dropped from 96.73% to 49.64%, and the degradation efficiency gradually decreased with the increase of initial concentration. This may be because too much MB will block the adsorption sites of the composite material and block the visible light on the solution surface, making it difficult to transmit, reducing the catalyst's absorption of light and resulting in a decrease in photocatalytic efficiency.
[0064] Then kinetic studies were performed, such as Figure 4 (bc), it can be seen that the degradation of the composite material conforms to the first-order kinetic curve, and the initial concentration is 10 mg L-1 The kinetic constant is the largest, k = 0.01428min -1 , respectively 15 mg L -1 (0.00440min -1 ), 20mg L -1 (0.00377min -1 ), 25mg L -1 (0.00306min -1 ) and 30 mg L -1 (0.00256min -1 )’s 3.25 times, 3.79 times, 4.67 times and 5.58 times.
[0065] The pH of the solution will affect the charge properties and adsorption capacity of the MNM surface, thereby affecting the ability of MNM to adsorb MB. Figure 5 As shown in (a), 30 mg of MNM catalyst was added to 100 mL of 10 mg L -1 MB solution, it can be seen that when the initial solution concentration pH value is 3, 5, 7, 9, 11, the MNM photocatalytic degradation efficiency is 50.57%, 78.32%, 96.74%, 95.39% and 99.47%, respectively. When pH = 11, the photocatalytic degradation efficiency of MNM is 10 mg L -1 The MB degradation rate reached the highest.
[0066] Since MB exists in the form of positive ions in the solution, when the solution is acidic, the catalyst surface will adsorb H + As a result, it becomes positively charged, which repels MB positive ions. The electrostatic repulsion is not conducive to the adsorption of pollutants by the catalyst, thereby reducing the degradation efficiency. When the solution is alkaline, the catalyst surface is negatively charged, and the electrostatic adsorption enhances the adsorption of the catalyst.
[0067] Next, the degradation kinetics were studied, e.g. Figure 5 As shown in (bc), it can be seen that the degradation efficiency reaches the highest when pH = 11.
[0068] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue, characterized in that: The steps include: Step 1: Preparation of Ni-MOLs Nickel nitrate hexahydrate and terephthalic acid were added to N,N-dimethylformamide, deionized water containing NaOH was slowly added, magnetic stirring was performed until dissolved, the mixture was transferred to a reactor for reaction, and the light green precipitate was collected by centrifugation, washed with deionized water and anhydrous ethanol respectively, and dried to obtain Ni-MOLs; Step 2: Preparation of MoS2 / Ni-MOLs MOLs, Na2MoO4·2H2O and TAA were weighed, added into ultrapure water, transferred to a reactor for reaction, black precipitate was collected by filtration, washed repeatedly with ethanol and ultrapure water, and dried to obtain 0.5MoS2 / Ni-MOLs, MoS2 / Ni-MOLs and 1.5MoS2 / Ni-MOLs.
2. The method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue according to claim 1, characterized in that: In the step 1, the concentration of nickel nitrate hexahydrate is 6 mmol, the concentration of terephthalic acid is 4 mmol, and the amount of N,N-dimethylformamide added is 150 mL.
3. The method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue according to claim 1, characterized in that: In the step 1, the concentration of NaOH is 0.32 mmol, and the amount of deionized water added is 10 mL.
4. The method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue according to claim 1, characterized in that: In the step 1, the reaction temperature of the reactor is 120° C. and the reaction time is 10 h.
5. The method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue according to claim 1, characterized in that: In the step 1, the rotation speed is 8000 rpm; and the mixture is washed three times with deionized water and three times with anhydrous ethanol respectively.
6. The method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue according to claim 1, characterized in that: In step 1, the drying temperature is 60° C. and the drying time is 12 h.
7. The method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue according to claim 1, characterized in that: In the step 2, the amount of MOLs added is 0.1 g; the amount of ultrapure water is 50 mL.
8. The method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue according to claim 1, characterized in that: In the step 2, TAA is specifically a mass ratio of MOLs:MoS2=2:1, 2:2, 2:
3.
9. The method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue according to claim 1, characterized in that: In the step 2, the reaction temperature of the reactor is 200° C. and the reaction time is 8 hours.
10. The method for preparing a MoS2 / Ni-MOLs heterojunction for promoting the degradation of an organic dye methylene blue according to claim 1, characterized in that: In step 2, the drying temperature is 60° C. and the drying time is 12 h.